Geographic and Temporal Trends in Amazonian Knowledge Production. (29th November 2013) - Malhado, Ana C. M.; de, Rafael S. D.; Todd, Peter A.; Santos, Ana M. C.; Fabré, Nídia N.; Batista, Vandick S.; Aguiar, Leonardo J. G.; Ladle, Richard J.
Abstract The presence of researchers from Western (i.e., developed world) institutions in Amazonia has frequently been contentious due to fears of 'scientific imperialism' or suspicions that they may be exerting undue influence over research agendas and knowledge production to the detriment of local researchers. Such negative perceptions are widespread, but not well substantiated. A more nuanced understanding of these issues requires information on who is conducting research in Amazonia and how knowledge production has changed over time. We performed a bibliometric analysis on Thomson Reuters'ISI Web of Science of all research articles about the Amazon published in three time periods: 1986–1989, 1996–1999, and 2006–2009. We found that the number of articles published and the diversity of countries involved in Amazonian research increased dramatically over the three time periods. The representation of several Amazonian countries—especially Brazil—increased, while the proportion of articles without a single author from an Amazonian country also increased. The results indicate that the research capacity of Amazonian countries has increased, but that leadership of high‐impact projects may still largely reside with researchers from developed countries.